Synthesis and the 5-HT6 receptor antagonistic effect of 3-arylsulfonylamino-5,6-dihydro-6-substituted pyrazolo[3,4]pyridinones for neuropathic pain treatment - Devegowda, Vani Nelamane; Hong, Jin-Ri; Cho, Sungjin; Lim, Eun Jeong; Choo, Hyunah; Keum, Gyochang; Rhim, Hyewon; Nam, Ghilsoo (Pergamon Press Ltd., 2013)
A novel series of 3-arylsulfonylamino-5,6-dihydro-6-substituted-1H-pyrazolo[3,4-c]pyridine-7-ones was designed and synthesized as 5-HT6 ligands. Among the derivatives synthesized, the lead compound, 12b, having piperidine functionality at the 6-position and (1-naphthyl)sulfonamino at the 3-position of the core structure showed the most potent 5-HT6 inhibitory activity in vitro, good stability without CYP liability, and good neuropathic pain alleviation activity in a rat animal model. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: SEROTONIN; DERIVATIVES; BINDING; MODEL